The Analysis of Speaking Assessment Types in Textbook “When English Rings a Bell Grade VII” - Putri Aulia Swastika; Ririt Rachma Miranti; Muhammad Rauuf Oktavian Nur (Jurnal Studi Guru dan Pembelajaran, 2020)
Speaking can be said as one of the four basic skills in English. In every English textbook, there must be a speaking assessment. This research aims to analyze the five types of speaking assessments in the textbook “When English Rings a Bell for Grade VII”. The textbook analysis in this study considered five types in speaking assessment there are: 1. Imitative speaking tasks, 2. Intensive speaking tasks, 3. Responsive speaking tasks, 4. Interactive speaking tasks and, 5. Extensive speaking tasks. This study includes the design of descriptive qualitative. This study using a method of content analysis. The collection of the data was done through procedures: 1) looking, 2) observing, 3)analyzing the data based on Brown’s theory. The result of the study there are five types of speaking tasks in that textbook, but it has a different rate of the types. The textbook not only has a speaking task, it also has another skill of English there are reading, listening, and writing.